2020
DOI: 10.1186/s12913-020-05511-z
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the consequences of decentralization: has privatization of health services been the perceived effect of decentralization in Khartoum locality, Sudan?

Abstract: Background: The health system of Sudan has experienced several forms of decentralization, as well as, a radical reform. Authority and governance of secondary and tertiary health facilities have been shifted from federal to state levels. Moreover, the provision of health care services have been moved from large federal tertiary level hospitals such as Khartoum Teaching Hospital (KTH) and Jafaar Ibnoaf Hospital (JIH), located in the center of Khartoum, to smaller district secondary hospitals like Ibrahim Malik (… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Finally, this study was limited to the public dispensaries of Khartoum state, which supplies the bulk of Sudan’s health services, and contains 25% of PHC facilities [ 43 ], due to the unfortunate centralized distribution. On the other hand, rural regions are home to 66.8% of the Sudanese population [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Finally, this study was limited to the public dispensaries of Khartoum state, which supplies the bulk of Sudan’s health services, and contains 25% of PHC facilities [ 43 ], due to the unfortunate centralized distribution. On the other hand, rural regions are home to 66.8% of the Sudanese population [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Localities are responsible for delivering primary health care services and aggregating health services by facilities in their districts. 32 …”
Section: Methodsmentioning
confidence: 99%
“…A study of healthcare expenditure and outcomes has shown that healthcare expenditure was positively associated with life expectancy and negatively associated with neonatal, infant, and under five death [ 15 ]. A major move towards decentralization and privatization of the health system during the dictatorship made access to quality healthcare very difficult and created a barrier to any development efforts in the country [ 16 , 17 ]. Significant decreases in expenditure on the public health system by the dictatorship deprived poor people from access to health services because they could not afford the cost of private health services.…”
Section: Introductionmentioning
confidence: 99%